2022
DOI: 10.1007/s00520-022-07294-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health and wellbeing among female pelvic cancer survivors following individualized interventions in a nurse-led clinic

Abstract: Purpose Treatment-induced sexual and intestinal dysfunctions coexist among women after pelvic radiotherapy. We aimed to explore if sexual health and wellbeing may be improved after radiotherapy following nurse-led interventions and if an association exists between improved intestinal health and sexual health. Methods A population-based cohort of women treated with pelvic radiotherapy underwent interventions at a nurse-led clinic at Sahlgrenska University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A statistically significant improvement was found over time in the patient’s sexual functioning in 11 studies, mostly in studies among individual patients. Of these, five studies based their intervention on PLISSIT [ 38 , 48 , 50 , 54 , 59 ]. One study among couples indicated improvement in female sexual functioning and little improvement in male sexual functioning, without providing information about significance [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A statistically significant improvement was found over time in the patient’s sexual functioning in 11 studies, mostly in studies among individual patients. Of these, five studies based their intervention on PLISSIT [ 38 , 48 , 50 , 54 , 59 ]. One study among couples indicated improvement in female sexual functioning and little improvement in male sexual functioning, without providing information about significance [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, seven studies reported a statistically significant improvement over time in overall quality of life [ 38 , 42 , 51 , 54 , 56 , 57 , 66 ]. Of these, three studies based their intervention on PLISSIT, which was applied to individual patients [ 38 , 54 , 66 ]. The remaining ten studies did not report a significant difference in overall quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations